Potentially antibreast cancer enamidines via azide–alkyne–amine coupling and their molecular docking studies. Issue 93 (21st September 2016) - Bansode, Prakash; Jadhav, Jagannath; Kurane, Rajanikant; Choudhari, Prafulla; Bhatia, Manish; Khanapure, Sharanabasappa; Salunkhe, Rajashri; Rashinkar, Gajanan
Abstract : Potentially antibreast cancer enamidines were synthesized and evaluated against human breast cancer cell line MCF7 displaying GI50 values lower than doxorubicin. Abstract : An attempt to prepare a new triazole series by Cu catalyzed multicomponent reactions of tosyl azide, propargyl bromide and secondary amines led to the synthesis of enamidines. All the synthesized enamidines were evaluated for antiproliferative activities. The four molecules4a–c and4h showed higher anticancer activity with GI50 values less than the standard drug doxorubicin against human breast cancer cell line MCF-7. The virtual analysis ascertains the mode of action of these compounds via inhibition of human cell division protein kinase7 (CDK7).